Design of high-performance dye-sensitized solar cells by variation of the dihedral angles of dyes. Issue 51 (22nd December 2016) - Kim, Kwang-Myeong; Hong, Jong-In
Abstract: Two new metal-free organic sensitizers (i.e., IAH and IDH) based on a D−π−A configuration were designed to elucidate the effect of the alkyl chain location at the thiophene π-bridge on their photovoltaic performance. IAH, in which the alkyl chain is closer to the acceptor moiety, is more planar than IDH, in which the alkyl chain is closer to the donor moiety. Therefore, IAH induces more effective π-conjugation and electron injection from the dye excited state to the TiO2 conduction band, leading to a higher short-circuit photocurrent (Jsc ). In contrast, IDH more effectively inhibits electron transfer from the conduction band of TiO2 to the dye excited state, resulting in a higher open-circuit photovoltage (Voc ). Under standard AM 1.5 simulated sunlight, the IAH-based cells exhibited an overall conversion efficiency of 6.90%; this value is higher than that of the IDH-sensitized cells, which reached 86% of the conversion efficiency of N719 cells. Graphical abstract: